Первое обнаружение неоаплектан (Nematoda, Steinernematidae), паразитирующих в слепнях - Pубцов, И.А.; Полевик, Н.Л. (Вестник зоологии, 1979)
The article deals with description and drawings of the new species, Neoaplectana tabanivora sp. n., obtained from Tabanus bromius. Some ideas are advanced on possibility of its using as an agent of biological gad flies control in the system of integrated measures.